Smart City Approaches to Public Spaces and Services during and after COVID-19: Case Studies in Four Capital Cities - Rachmawati, Rini; Mei, Estuning Tyas Wulan; Haryono, Eko; Reinhart, Hilary; Ghiffari, Rizki Adriadi; Rohmah, Amandita Ainur; Saralah, Thas; Pradipa, Hanindha; Nurani, Idea Wening; Petre, Angelo Andi (Indonesian Journal of Geography, 2023)
COVID-19 pandemic was reported to modify people’s behaviour in using public spaces and accessing services. This fact has become a critical input related to future city development strategies, space arrangements, and the implementation of smart city. Therefore, this study aims to 1) Identify efforts in several cities during COVID-19 pandemic, specifically concerning the use of public spaces and services, and 2) Compile the outlines of future urban planning strategies after the pandemic. The aspects related to the use of Information and Communication Technology (ICT), space arrangement, and urban environment are discussed. The analysis is based on case studies in four capital cities, namely Jakarta, Paris, Bucharest, and Canberra. Furthermore, field observations and in-depth interviews are used to emphasize changes in the function and use of public spaces and services during and after the pandemic. The result shows that differences and common elements configure the transformations of urban spaces since changes in the use of public spaces are closely connected to efforts to combat the pandemic. Meanwhile, in public services, changes are associated with the increasing use of ICT and Internet of Things (IoT). In the future, cities need to show their visions according to the local conditions supporting better spatial arrangement and management of urban environment due to ICT and IoT prominence.